Hubungan Antara Tingkat Keterlibatan Siswa Dalam Pembelajaran Fisika dan Hasil Belajar Fisika Siswa Kelas X di SMA N 1 Padang Bolok Julu - Rahmad Fadila Ritonga; Eni Sumanti Nasution; Kasmawati (JURNAL PENDIDIKAN ILMU PENGETAHUAN ALAM, 2025)
This study aims to analyze the relationship between student engagement in physics learning and the academic achievement of Grade X students at SMA Negeri 1 Padang Bolak Julu. The research employs a quantitative correlational design, involving 32 students as respondents. Student engagement data were measured using a validated questionnaire, while academic achievement was assessed through performance tests. The analysis results indicate an average student engagement score of 78.22, with the majority of students categorized as moderate. The average physics learning achievement score was 81.91, reflecting good performance. Pearson correlation analysis revealed a correlation coefficient of 0.712 with a significance value of 0.018, indicating a significant positive relationship between student engagement and physics learning outcomes. These findings emphasize the importance of active student participation in enhancing academic performance. This research is expected to provide insights for teachers in designing more effective learning strategies.